Exploration of the procedures and practices for providing student support services in a nursing college in South Africa (Journal of Student Affairs in Africa, 2024)
The shortage of nurses is a global crisis, particularly in remote and rural communities. Contributory factors are retirements, resignations, recent increased deaths due to the COVID-19 pandemic, and the reduced production of nurses because of high attrition rates. This article’s purpose was to investigate the provision of student support in the nursing education institution (NEI) of the KwaZulu-Natal (KZN) province in South Africa and come up with a model to improve completion rates. The researchers intentionally selected three KZN campuses based on their demographical location and programme offerings for the study. For data collection through in-depth interviews, the study adopted a case study design and employed a qualitative explorative approach, purposely sampling the NEI’s senior academic staff. Strauss and Corbin’s stages of coding were used to conduct the data analysis. The findings suggest comprehensive orientation and academic support as strong measures applied by the NEI to provide student support services and highlighted a need to improve enabling resources. Psychosocial support was predominantly provided by the hospital, which implied a lack of on-site comprehensive support. A necessity for developing a comprehensive student support model for the NEI emerged from the study. The model is expected to enhance the support and, in turn, increase completion rates.
Keywords: comprehensive student support; attrition; academic success; nursing education institution; psycho-social support